ADAMTS-4 promotes neurodegeneration in a mouse model of amyotrophic lateral sclerosis. Issue 1 (December 2016) - Lemarchant, Sighild; Pomeshchik, Yuriy; Kidin, Iurii; Kärkkäinen, Virve; Valonen, Piia; Lehtonen, Sarka; Goldsteins, Gundars; Malm, Tarja; Kanninen, Katja; Koistinaho, Jari
Abstract Background A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) proteoglycanases are specialized in the degradation of chondroitin sulfate proteoglycans and participate in mechanisms mediating neuroplasticity. Despite the beneficial effect of ADAMTS-4 on neurorepair after spinal cord injury, the functions of ADAMTS proteoglycanases in other CNS disease states have not been studied. Therefore, we investigated the expression, effects and associated mechanisms of ADAMTS-4 during amyotrophic lateral sclerosis (ALS) in the SOD1G93A mouse model. Results ADAMTS-4 expression and activity were reduced in the spinal cord of SOD1G93A mice at disease end-stage when compared to WT littermates. To counteract the loss of ADAMTS-4, SOD1G93A and WT mice were treated with saline or a recombinant ADAMTS-4 before symptom onset. Administration of ADAMTS-4 worsened the prognosis of SOD1G93A mice by accelerating clinical signs of neuromuscular dysfunctions. The worsened prognosis of ADAMTS-4-treated SOD1G93A mice was accompanied by increased degradation of perineuronal nets enwrapping motoneurons and increased motoneuron degeneration in the lumbar spinal cord. Motoneurons of ADAMTS-4-treated SOD1G93A mice were more vulnerable to degeneration most likely due to the loss of their extracellular matrix envelopes. The decrease of neurotrophic factor production induced by ADAMTS-4 in vitro and in vivo may also contribute to a hostile environment for motoneuron especially when devoid of a net. Conclusions This study suggests that the reduction of ADAMTS-4 activity during the progression of ALS pathology may be an adaptive change to mitigate its neurodegenerative impact in CNS tissues. Therapies compensating the compromized ADAMTS-4 activity are likely not promising approaches for treating ALS.